Synthesis of Polyol As Lubricant Base Via Epoxydation and Hydroxylation Reactions of Moringa oleifera Seed Oil - Ade Danova; Daniel Tarigan; Erwin - (PROSIDING SEMINAR KIMIA, 2015)
Moringa oleifera seed oil has potential as a base material in the synthesis of polyol, because the most content of fatty acid was oleic acid (up to70.7167%). Polyol could be used as a lubricant base. Polyol research of Moringa oleifera seed oil had been done via epoxidation and hydroxylation of one step reaction, where the polyol was characterizated by FT-IR spectroscopy shown absorption –OH group in the number of wave 3379.29 cm-1 and the number of iodine with iodometri methods that decreased from 107.3769 to 3.6755 mg I/g. Quality polyol test as a lubricant base consists of specific gravity (0,978), kinematic viscosity (216.702 cSt at 40oC and 21.116 cSt at 100oC) and viscosity index (111.013). Where they could be reported on the test results that the seeds of Moringa oleifera oil polyol was better than Moringa oleifera seed oil to use as a lubricant base, because it had committed with quality SAE J306 standards and classification SAE in manual gear oil, transmission and axle in lubricants group SAE 90 based to result from kinematic viscosity at 100oC.